Impact of hypnosis on psychophysiological measures: A scoping literature review. Issue 1 (15th October 2021) - Fernandez, Aurore; Urwicz, Leah; Vuilleumier, Patrik; Berna, Chantal
ABSTRACT: Exploring psychophysiological changes during hypnosis can help to better understand the nature and extent of the hypnotic phenomenon by characterizing its influence on the autonomic nervous system (ANS), in addition to its central brain effects. Hypnosis is thought to induce a relaxation response, yet studies using objective psychophysiological measures alongside hypnosis protocols show various results. We review this literature and clarify the effects of hypnosis on psychophysiological indices of ANS activity and more specifically of the stress/relaxation response, such as heart rate variability and electrodermal activity. Studies reporting psychophysical measures during hypnosis were identified by a series of Pubmed searches. Data was extracted with an interest for the influence of hypnotizability and effects of specific suggestions or tasks on the findings. We found 49 studies comprising 1315 participants, 45 concerning healthy volunteers and only 4 on patients. Sixteen compared high vs. low hypnotizable people; 30 measured heart rate, 18 measured heart rate variability, 25 electrodermal activity, and 23 respiratory signals as well as other physiological parameters. Globally, results converge to show reductions in sympathetic responses and/or increases in parasympathetic tone under hypnosis. Several methodological limitations are underscored, such as older studies (N = 16) using manual analyses, small sample sizes (<30, N = 31), as well as uncontrolled multiple comparisons. Nevertheless, we confirm that hypnosis leads to a physiological relaxation response and highlight promising avenues for this research. Suggestions are made for guiding future work in this field.